Analysis and Comparison of the DC-DC converter with soft Computing algorithm - Goswami, Agam Das; Hole, Shreyas R (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Due to technological discoveries in power generation or other power sources, DC-DC converters have developed more practical uses in electrical generation technologies (especially in DC micro grids). Separate the conversion components and generation of an optimized separate predictive algorithm may be achievable through model parameters. The primary goal of implementing an electronic parts converter for grid connection is to provide an amount of energy statistically and quantitatively satisfactory for the many applications at hand. Load frequency control electronics are divided into transistors, DC-to-DC converts, and rectifier diodes. The adapter from DC - DC is frequently used even among the many. The proposed technique can be applied to other parameter verification and improvement conditions, such as rectifier circuits, filter power supplies, etc.